Cancer prevalence by phase of care: an indicator for assessing health service needs. Issue 4 (August 2021) - Gigli, Anna; Francisci, Silvia; Guzzinati, Stefano; Hall, Aaron; Hachey, Mark; Scoppa, Steve; Mariotto, Angela
Introduction: Cancer prevalence (people alive on a certain date in a population who previously had a cancer diagnosis) is expected to increase in the United States and Europe due to improvements in survival and population aging. Examination of prevalence by phase of care allows us to identify subgroups of patients according to their care trajectories, thus allowing us to improve health care planning, resource allocation, and calculation of costs. Methods: A new method to estimate prevalence by phase of care using grouped data is illustrated. Prevalence is divided into 3 mutually exclusive phases: initial, continuing, and end-of-life. An application to US and Italian data is applied to prevalent cases diagnosed with colon–rectum, stomach, lung, or breast cancer. Results: The distribution of phase of care prevalence estimated by cancer type and sex and results from the two datasets are very similar. Most survivors are in the continuing phase; the end-of-life phase is larger for cancers with worse prognosis. All phases prevalence is generally higher in the Italian than in the US dataset, except for lung cancer in women, where prevalence proportion in the Italian dataset is 30% lower than in the United States. Discussion: Incidence, survival, and population age structure are the main determinants of prevalence and they can affect differences in all phases of prevalence, as well as in discrete phases. Incidence is the most influential determinant. Ours is the first study that compares prevalence by phase of care between two populations in Italy and the United States. Despite great differences in health care management in the two countries, we found extremely similar distribution of survivors by phase of care for most cancer sites under study.